Striatal functional connectivity changes following specific balance training in elderly people: MRI results of a randomized controlled pilot study - Magon, Stefano; Donath, Lars; Gaetano, Laura; Thoeni, Alain; Radue, Ernst-Wilhelm; Faude, Oliver; Sprenger, Till (Gait & posture, 2016)
•Slackline training leads to task-specific improvements of slackline performance.•Improved balance performance goes along with reduced striatal connectivity.•Slackline training did not induced relevant changes of brain morphology. Practice-induced effects of specific balance training on brain structure and activity in elderly people are largely unknown. In the present study, we investigated morphological and functional brain changes following slacking training (balancing over nylon ribbons) in a group of elderly people. Twenty-eight healthy volunteers were recruited and randomly assigned to the intervention (mean age: 62.3±5.4years) or control group (mean age: 61.8±5.3years). The intervention group completed six-weeks of slackline training. Brain morphological changes were investigated using voxel-based morphometry and functional connectivity changes were computed via independent component analysis and seed-based analyses. All analyses were applied to the whole sample and to a subgroup of participants who improved in slackline performance. The repeated measures analysis of variance showed a significant interaction effect between groups and sessions. Specifically, the Tukey post-hoc analysis revealed a significantly improved slackline standing performance after training for the left leg stance time (pre: 4.5±3.6s vs. 26.0±30.0s, p<0.038) as well as for tandem stance time (pre: 1.4±0.6s vs. post: 4.5±4.0s, p=0.003) in the intervention group. No significant changes in balance performance were observed in the control group. The MRI analysis did not reveal morphological or functional connectivity differences before or after the training between the intervention and control groups (whole sample). However, subsequent analysis in subjects with improved slackline performance showed a decrease of connectivity between the striatum and other brain areas during the training period. These preliminary results suggest that improved balance performance with slackline training goes along with an increased efficiency of the striatal network.